The Influence Of Ratio Chocolate With Dadih To The Quality Of Sensory Praline Dadih - Aimuni, Nurul; Faridah, Anni (Universitas Negeri Padang, 2023)
Lack of public knowledge of west Sumatra's typical functional food, namely